Production of Lipid Microparticles Magnetically Active by a Supercritical Fluid-Based Process. (5th July 2009) - Vezzù, Keti; Campolmi, Chiara; Bertucco, Alberto
Abstract : An original technique, based on supercriticalCO 2 and on the particles from gas saturated solution (PGSS) micronization method, was developed to obtain magnetically active lipid microparticles. Magnetite nanoparticles (MNPs) were encapsulated into triestearin and phosphatidylcholine mixtures to increase their biocompatibility for future applications in the fields of biomedical diagnostics and therapeutic medications. The lipid particles produced were characterized to determine size and size distribution, and to confirm the encapsulation of MNP. The mean size was in the range of 200–800 nm. The possibility to drive these magnetically active particles by an external magnet was demonstrated in a simple apparatus simulating a vessel of the circulatory system. The results obtained indicate that the modified PGSS technique is suitable to produce lipid microparticles with magnetic activity for possible use in medical applications.